Participação social : uma realidade nos processos de gestão da Política de Assistência Social em municípios do Rio Grande do Sul? - Flores, Ana Paula Pereira (2016)
The following study demonstrates the results of the research developed during the realization of a master's thesis in Social Services in the Postgraduate Program of the School of Humanities of PUCRS, who had as a primary focus to identify how, and if, the social participation, primarily through the Conferences of Social Assistance, can materialize itself and exert influence in the management and execution of the Social Assistance Politics, especially as a parameter in the elaboration of the main instrument of planning of this public politic, independent of which is the Plan of Social Assistance. In the definition of the counties that would participate in the research, there was an effort to include initially 5 counties of different population densities, in accordance with the classification through the size of the population by the Nacional Politic of Social Assistance (BRASIL, 2004). In this sense, an endeavor was made in the search of information on the counties management, with the objective to verify if the social participation, mainly through the Conferences of Social Assistance, can exercise influence in the process of planning this public politic, as an expression of the public will and the forums of deliberation and social participation. To attain the objectives of this study, the critical dialectical method was chosen. The data was analyzed through the categories of the method: historicity, contradiction and totality. Also used as explanatory categories of the reality: Social Participation, the Social Assistance Politic, the Unified System of Social Assistance (SUAS), the Public Conferences, the Counties Plan of Social Assistance and the Access to Information. The study is descriptive and of qualitative nature. For the research procedures the used technique was documentary analysis. However, in the investigation process, there was a great difficulty of access of the documents to be researched, in this case, the Counties Plan of Social Assistance (PMAS), which demonstrated a fragility in the social control of the researched counties, as well as difficulties in dealing with the transparency of public data, by the counties management of the Social Assistance Politic. In this way, there were already preliminary difficulties to the exercise of social participation through the citizens, and yet, an evident incoherence as regards to the transparency of public information of this politic, taking into account the recommendations of SUAS and the Federal Law nº 12.527, of November 18, 2011 – Law of Information Access (LAI) (BRASIL, 2011), which regulates the constitutional access of information, to be observed by the public agencies of direct and indirect management of all powers of the Union, the States, the DF and the Counties. In this manner, a debate is necessary to be made about how the social participation is being outlined and materialized as a main instrument of local planning of the Social Assistance Politic, as well as the public transparency of information inherent to it, considering that this issues are in a determinate and undeniable moment of construction and fortification in Brazil.